The abuse of police power in investigating suspects in criminal offences / Ferrinow Kadri, Khalijjah Mohd. Khalid and Mohammad Ikraam Mohd Noor - Kadri, Ferrinow; Mohd. Khalid, Khalijjah; Mohd Noor, Mohammad Ikraam (2006)
The Royal Malaysia Police has endured the joy and ecstasy, pain and suffering of overseeing a nation grow and prosper. The achievement of the RMP could not be put aside or squash away. The RMP has help Malaysia tremendously during the communist insurgency and the Emergency. Yet, the image and the reputation of RMP is slowly deteriorating and worsening only because several individuals which is believe to be involved in the misuse and abuse of police powers. The issue of abuse of police power is very real in Malaysia as it concerned with the public interest and the public confidence. Hence, there is a need to understand the real power of the police pertaining to the conduct of investigation, the manner of which it is done, the extent of its discretionary power and the abusive matters. This particular research is aimed to give better understanding and comprehension to the public on the matters relating to the power of the police as it look into the statutory and discretionary power of the police and, how, when, why the abuse happens.. Furthermore, the research looks into depth the process of the investigation which are, arrest, detain, search, and interrogation in the Criminal Procedure Code, Police Act and the Lock up Regulation. The research recommends that there must be reassessment of the relevancy of such statutes. The research also would like to propose to the amendment of the Criminal Procedures Code, Police Act and Lock up Regulation as it only prescribed the general discretionary power of the police, and not the manner of implementing such powers. Lastly, the research would like to suggest that the RMP should be more transparent in dealing with the public as ambiguity creates fearness.